2017
DOI: 10.3126/on.v14i1.16435
|View full text |Cite
|
Sign up to set email alerts
|

Effect of disturbance on litter dynamics in moist tropical forest of eastern Nepal

Abstract: Litterfall is an important vector of nutrient and carbon recycling in forest ecosystems. Present study was conducted in moist tropical forest of eastern Nepal to understand the effect of disturbance on litter dynamics. Litterfall was estimated at monthly intervals from one litter trap (1 m × 1 m) at each of the 70 sampling plots while litter mass accumulated at each sampling plot was collected once every season from one 1 m × 1 m plot. The total annual litterfall in undisturbed forest (UF) was 11.8 Mg ha −1 yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In eastern Democratic of the Congo (DRC), Cassart et al () reported that leaves accounted for 63%–66% of total litterfall. Leaf litter comprised 75%–87% of total litterfall in an undisturbed tropical moist forest in eastern Nepal and 81%–90% in a disturbed forest (Gautam & Mandal, ).…”
Section: Discussionmentioning
confidence: 99%
“…In eastern Democratic of the Congo (DRC), Cassart et al () reported that leaves accounted for 63%–66% of total litterfall. Leaf litter comprised 75%–87% of total litterfall in an undisturbed tropical moist forest in eastern Nepal and 81%–90% in a disturbed forest (Gautam & Mandal, ).…”
Section: Discussionmentioning
confidence: 99%
“…The process of decomposition is primarily carried out by bacteria and fungi, thus the rate of decomposition entirely depends on microbial activities which in turn, get affected by soil character and climatic condition in an area (Berg and McClaugherty, 2014). Moreover, Gautam and Mandal (2016) have also reported the effect of disturbance on litter dynamics in a moist tropical forest. Litter mass loss or decay is the sum of carbon dioxide release and discharge of compounds that contains both carbon compounds and nutrients (Brady and Weil, 2010).…”
mentioning
confidence: 99%